PDCD1 Polymorphisms May Predict Response to Anti-PD-1 Blockade in Patients With Metastatic Melanoma - Parakh, Sagun; Musafer, Ashan; Paessler, Sabrina; Witkowski, Tom; Suen, Connie S. N. Li Wai; Tutuka, Candani S. A.; Carlino, Matteo S.; Menzies, Alexander M.; Scolyer, Richard A.; Cebon, Jonathan; Dobrovic, Alexander; Long, Georgina V.; et al. (Frontiers in Immunology, 2021)
A significant number of patients (pts) with metastatic melanoma do not respond to anti-PD1 therapies. Identifying predictive biomarkers therefore remains an urgent need. We retrospectively analysed plasma DNA of pts with advanced melanoma treated with PD-1 antibodies, nivolumab or pembrolizumab, for five PD-1 genotype single nucleotide polymorphisms (SNPs): PD1.1 (rs36084323, G>A), PD1.3 (rs11568821, G>A), PD1.5 (rs2227981, C>T) PD1.6 (rs10204225, G>A) and PD1.9 (rs2227982, C>T). Clinico-pathological and treatment parameters were collected and presence of SNPs correlated with response, progression free survival (PFS) and overall survival (OS). 115 patients were identified with a median follow up of 18.7 months (range 0.26 – 52.0 months). All were Caucasian; 27% BRAF V600 mutation positive. At PD-1 antibody commencement, 36% were treatment-naïve and 52% had prior ipilimumab. The overall response rate was 43%, 19% achieving a complete response. Overall median PFS was 11.0 months (95% CI 5.4 - 17.3) and median OS was 31.1 months (95% CI 23.2 - NA). The G allele of PD1.3 rs11568821was significantly associated with a better ORR compared to the A allele (p=0.034; 95% CI 0.14 – 0.94). Patients with the G/G genotype had more complete responses than with A/G genotype (16.5% vs. 2.6% respectively) and the GG allele was associated with a longer median PFS than the AG allele, 17.9 vs. 7.0 months. No significant association between the remaining SNPs and responses were observed. This is the first study to demonstrate an association of a germline PD-1 polymorphism and response to anti-PD-1 therapy in pts with metastatic melanoma. Extrinsic factors like host germline polymorphisms should be considered with tumour intrinsic factors as predictive biomarkers for immune checkpoint regulators.